다문화 가정 의사소통 지원에 대한 언어치료 전공자의 인식 연구 - 김민성(Min Sung Kim); 김시현(Si Hyun Kim); 김화수(Wha Soo Kim) (언어치료연구, 2018)
목적: 본 연구는 다문화 가정 의사소통 지원에 대한 언어치료 전공자의 경험 및 인식을 알아보고, 다문화 사회에서 의사소통 지원의 중요성과 나아갈 방향을 제고하고자 하였다. 방법: 전국의 언어치료 전공자 172명을대상으로 구글 모바일 설문 조사를 실시하였다. 설문지의 구성은 대상자의 일반적 특성 7항목, 다문화 가정의사소통 지원 관련 경험 6항목, 다문화 가정 의사소통과 관련한 인식 7항목, 다문화 아동 및 부모 지원 장벽에 대한 인식 18항목, 지원 방안에 대한 요구 8항목으로 이루어졌다. 결과: 첫째, 다문화 가정 의사소통에 대한 지원 경험에서 다문화 의사소통 과목 수강은 대상자의 58.7%가 경험이 있는 것으로 나타났다. 이와 함께다문화 가정 아동의 언어 치료 및 부모 상담 경험은 47.7%가 지원 경험이 있는 것으로 나타났다. 둘째, 다문화 가정 아동의 언어차이 요인에 대하여 언어자극 결핍이 원인이라고 인식하였다. 또한, 언어차이 영역은 음운론 차이가 큰 것으로 응답하였다. 의사소통 지원 시 우선 선정할 목표 언어에 대하여 한국어를 우선 지도해야 한다는 인식이 가장 높았으며, 효율적인 지원형태로는 부모-아동 상호작용 지원이 가장 빈도가 높았다. 셋째, 다문화 가정 의사소통의 지원 장벽에 대한 인식은 아동 치료보다 부모 상담에서 장벽이 더 높은 것으로볼 수 있었다. 넷째, 다문화에 기반한 표준화된 언어평가 도구 개발, 다문화 관련 바우처 서비스 확대 및 정보제공이 시급한 것으로 인식되었다. 결론: 다문화 가정 의사소통 지원을 위하여 개별 언어재활서비스 뿐만 아니라 그 부모 및 가정에 대한 국가의 제도 개선, 관련 협회의 교육 등 다각적인 협력이 강조된다. Purpose: This study investigated speech-language pathology (SLP) majors' experience in and perception on communication support for multicultural families and provided future implications and direction. Methods: A Google mobile questionnaire was conducted on 172 SLP majors across Korea. The questionnaire was composed of seven categories of general subject characteristics; six of experience relevant to communication support for multicultural families; seven of perception on communication with multicultural families; 18 of perception on multicultural children and barrier in parental support; and eight of requests for support policy. Results: Firstly, it was found that 58.7% of the subjects had experiences in taking multicultural communication class. Moreover, 47.7% said that they had experiences in providing speech therapy for children from multicultural families and parent counselling. Secondly, the subjects answered that the deficiency of linguistic stimulus is the main cause of linguistic differences shown in children from multicutural families; the principal part of this was differences in phonology. Korean language must be a priority to teach as a target language for communication support. For efficient support, interactional support for parent and children should be provided. Thirdly, in terms of perception of barriers in supporting multicultural communication, parent counselling is a greater barrier than child therapy. Fourthly, there was a perception that there is an urgent need for development of standard language evaluation tools based on multiculturism and expansion of voucher service related to multiculturism and information support. Conclusions: Not only individual language rehabilitation service but also multi-dimensional cooperation including improvement in government-level policy for multicultural families and parents and education by related associations are emphasized for communication support for multicultural families. KCI Citation Count: 2